2020
DOI: 10.3389/fnagi.2020.00148
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Senescence and Alzheimer’s Disease: A Review

Abstract: Astrocytes are the largest group of glial cells in the brain and participate in several essential functions of the central nervous system (CNS). Disruption of their normal physiological function can lead to metabolism disequilibrium and the pathology of CNS. As an important mechanism of aging, cellular senescence has been considered as a primary inducing factor of age-associated neurodegenerative disorders. Senescent astrocytes showed decreased normal physiological function and increased secretion of senescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 148 publications
(237 reference statements)
1
73
0
Order By: Relevance
“…In this study, we found that: (1) WT and AD mice showed different correlation patterns between Hip/PFC EEG activity and behavioral memory; (2) based on regression correlations, treatment with the GABA A antagonist bicuculline improved brain function in AD mice, but resulted in poorer brain function in WT mice; (3) treatment with the GABA A agonist muscimol benefited AD mice, but showed no obvious effects on WT mice.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this study, we found that: (1) WT and AD mice showed different correlation patterns between Hip/PFC EEG activity and behavioral memory; (2) based on regression correlations, treatment with the GABA A antagonist bicuculline improved brain function in AD mice, but resulted in poorer brain function in WT mice; (3) treatment with the GABA A agonist muscimol benefited AD mice, but showed no obvious effects on WT mice.…”
Section: Discussionmentioning
confidence: 80%
“…At present, the incidence of AD is 4% among individuals aged 65 and up to 40%-50% among individuals aged 85 (1,2). Evidence suggests that brain senescence contributes to AD pathogenesis (3,4), and a link exists between the aging process and disease development (5)(6)(7). As aging is an important risk factor for AD, it would be interesting to compare differences between AD and normal aging, and thus help clarify the neural mechanisms of AD.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in glial glutamate uptake capacity in SAMP8 may elevate extracellular glutamate levels, leading to neuronal excitotoxicity [ 85 ], and contribute to premature learning and memory deficits observed not only in this murine model of early aging but also of AD. In fact, astrocyte senescence and its putative role in the pathologic progress of AD has been recently reviewed [ 86 ]. Astrocytes cultured from neonatal SAMP8 mice present similar alterations to those described in the whole brains of SAMP8 mice at 1–5 months of age [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomographic amyloid imaging, cerebrospinal fluid tau and Aβ levels have high specificity in the diagnosis of AD. 5 However, they are expensive and timeconsuming.…”
Section: Introductionmentioning
confidence: 99%